2004
DOI: 10.1128/iai.72.7.4233-4239.2004
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Splenic Dendritic Cell Population to Malaria Infection

Abstract: Dendritic cells, particularly those residing in the spleen, are thought to orchestrate acquired immunity to malaria, but it is not known how the splenic dendritic cell population responds to malaria infection and how this response compares with the responses of other antigen-presenting cells. We investigated this question for Plasmodium chabaudi AS infection in C57BL/6 mice. We found that dendritic cells, defined here by the CD11c marker, migrated from the marginal zone of the spleen into the CD4 ؉ T-cell area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 34 publications
10
69
0
Order By: Relevance
“…The kinetics of DC uptake of pRBCs closely coincided with the level of IFN-␥ production observed in P. chabaudi-infected B6 mice (19,23). Notably, the peak level of pRBC uptake by splenic DCs observed in this study also coincided with peak numbers of splenic CD11c ϩ DCs expressing IFN-␥ at day 4 -5 following P. chabaudi infection (7,24). For macrophages, levels of nonopsonic phagocytosis also correlate with the ability of infected mice to produce IFN-␥ and treatment of macrophages with IFN-␥ in vitro enhances phagocytosis of pRBCs while treatment with IL-10 inhibits this activity.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The kinetics of DC uptake of pRBCs closely coincided with the level of IFN-␥ production observed in P. chabaudi-infected B6 mice (19,23). Notably, the peak level of pRBC uptake by splenic DCs observed in this study also coincided with peak numbers of splenic CD11c ϩ DCs expressing IFN-␥ at day 4 -5 following P. chabaudi infection (7,24). For macrophages, levels of nonopsonic phagocytosis also correlate with the ability of infected mice to produce IFN-␥ and treatment of macrophages with IFN-␥ in vitro enhances phagocytosis of pRBCs while treatment with IL-10 inhibits this activity.…”
Section: Discussionsupporting
confidence: 80%
“…This increased phagocytic activity may be due to an expansion of the DC population in the spleen following P. chabaudi infection (7,24). As the parasite replicates, causing the parasite burden to increase in the blood and more pRBCs to be deposited in the spleen for removal, blood-borne DCs are recruited to the spleen in increasing numbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we demonstrate that DCs from infected mice maintain their ability to activate naive T cells throughout infection, an issue that has been controversial. Although some studies show that DCs derived in vitro in the presence of parasitized RBC are dysfunctional (21,22), other work, including our own, found that DCs derived from infected mice are fully mature with respect to expression of costimulatory proteins and T cell activation (11,23,24). One possible explanation for the discrepant results is the lack of T cell-DC interaction in systems where DCs are matured in vitro.…”
Section: Late-stage Malaria Infection Results In Endotoxin Tolerance mentioning
confidence: 77%
“…Both these findings suggest depressed DC activity. In mouse studies, using murine-compatible Plasmodium species, iRBCs (schizonts or lysates thereof ) were able to stimulate murine mDCs to produce IL-12 and elicit T-cell activation [30], as well as DC surface expression of CD40 and CD86 and migration to T-cells zones in lymphoid tissue in vivo [31]. In contrast with such activation, another group showed hemozoin to impair murine DC function in lymphoid tissue, particularly DC:T-cell clustering, and generated poorly functional T cells [32,33].…”
Section: Dendritic Cells and Malariamentioning
confidence: 99%